(untitled) - Prof. Dr. Nikolaus Beck, University of Lugano, Switzerland; Prof. Dr. Frauke von Bieberstein, Universität Bern, Switzerland; Prof. Dr. Peter Fiechter, Universität Neuchâtel, Switzerland; Prof. Dr. Pascal Gantenbein, Universität Basel, Switzerland; Prof. Dr. Markus Gmür, Universität Fribourg, Switzerland; Prof. Dr. Stefan Güldenberg, EHL Hospitality Business School Lausanne (Managing Editor); Prof. Dr. Karsten Hadwich, Universität Hohenheim; Prof. Dr. Christine Legner, Universität Lausanne, Switzerland; Prof. Dr. Klaus Möller, Universität St. Gallen, Switzerland; Prof. Dr. Günter Müller-Stewens, Universität St. Gallen, Switzerland; Prof. Dr. Dieter Pfaff, Universität Zürich, Switzerland; Prof. Dr. Martin Wallmeier, Universität Fribourg, Switzerland (Die Unternehmung, 2021)
With its concept of linking theoretical claim with practical relevance in high-quality contributions Die Unternehmung counts as one of the leading German journals in the field of Business Administration. It covers all core subjects of business administration (e.g. marketing, accounting/controlling, organisation and corporate governance) as well as includes more recent fields such as technology and innovation management, logistics, and supply chain management. Die Unternehmung disseminates new academic insights, spotlights interesting problems from practice, presents academically profound solutions for practice, and generally encourages an exchange between science and practice. Website: www.unternehmung.nomos.de